Protecting the Right to Clean Water: Legal Challenges and Solutions for River Pollution in Kurdistan - Hiwa Rashid Ali; Asmar Abdul Rahim; Haslinda Mohd Anuar (Sriwijaya Law Review, 2025)
Access to clean water is a fundamental human right recognised by the United Nations. However, in Iraq, particularly in the Kurdistan region, this right is under significant threat due to severe pollution and contamination of rivers. While the Iraqi Constitution and environmental laws indirectly acknowledge the right to clean water, the legal and institutional framework for river protection remains inadequate. This study focuses on the Tanjero River as a case study to assess Iraq's legal framework and enforcement mechanisms for water resource protection. This study identifies critical gaps in legislation and enforcement through a qualitative and socio-legal methodology, including interviews and analysis of relevant laws such as Law No. 8 (2008) for Environmental Protection and Improvement. The findings reveal that the Tanjero River's pollution is primarily caused by mismanagement of water resources, insufficient legislation, weak enforcement, lack of coordination, and inadequate infrastructure. The Kurdistan Regional Government must prioritise sustainable water resource management, establish a comprehensive legal framework, and implement rigorous enforcement measures to address these issues. These steps are essential to safeguarding the right to clean water, protecting public health, and promoting sustainable development in the region.